Procedimento de observação de pareamento de estímulos: Efeitos da alternância de pareamentos e testes na aquisição de resposta de ouvinte e tatos em crianças com autismo - Ó, Lorraine Calandrini Araújo do (Universidade Federal do Pará, 2020)
Many of the opportunities for verbal repertoire learning occur in everyday interactions as children listen to other people talking about objects/events without demanding responses from them. A procedure that resembles this type of interactions is the Stimulus Pairing Observation Procedure (SPOP). The SPOP has recently been used to investigate verbal repertoire learning. Some studies have suggested that alternating SPOP and verbal repertoire tests (SPOP-test cycles) could favor the acquisition of verbal repertoires in children and adolescents with autism. The present study investigated, through a multiple probe design among participants with alternating treatments, the efficiency of the SPOP-test cycles compared to the SPOP implementation with tests only after a number of pairings equivalent to the pairings performed in the cycles, in the acquisition of tact and listener response in children with autism. The results demonstrated the efficacy of SPOP to induce the emergence of these repertoires in children with autism and that SPOP-test cycles are more efficient compared to SPOP implementation alone. The role of alternating pairings and tests on the effectiveness of SPOP and the importance of performing pre-tests of the different naming repertoires of individuals prior to SPOP implementation are discussed.